Anti-Inflammatory Effect of Red Piper Crocatum Leaves Extract Decrease TNF-? and IL-6 Levels in Wistar Rat with Atherosclerosis - Wahjuni, Sri; Wita, I W.; Astawa, I N. Mantik (BALI MEDICAL JOURNAL, 2016)
Background : This research aims to find a cure for anti-inflammation, based on the utilization of red piper crocatum. The research was started with descriptive study to explore active components of red piper crocatum leaf and  followed by experimental study to investigate red piper crocatum activity of the leaf extract in anti-inflammation  induced Wistar rat. In this research observed three dominant components: caryophyllene bicyclo [5.2.0] none, 2  methylene-4,8,8-trimethyl-4-vinyl; phytol; 5,9-propano-5H- benzocycloheptene, 6,7,8,9-tetrahydro-7,11- bis(methylene); 4,4-ethynedioxy-2-hexadecen-15-15 olide 1,4,9-trioxaspiro [4,15] eic os-6-en-8-one, 10 methyl; 1H- 1,2,4-triazole-5(H)-thione,4-allyl-3-(3-furyl); Benzofuran,2,3-dihydro-2-methyl-7-phenyl which are possibly active  to inhibit anti-inflammation to atherosclerosis. Bad eating habits also can cause various health problems, such as  obesity, dyslipidemia, inflammation to atherosclerosis. This study was conducted to investigate of red piper crocatum leaves extract as an anti-inflammation through decrease of biochemistry markers TNF- ? and IL-6 levels.  Method : This is a true experimental with randomized pre-test and post-test control group design, using 50 Wistar  rats that are divided into 5 groups: control group using 0 mg/kg B  red piper crocatum leaves extract, treatment  group 1 using 50 mg/kg BW red piper crocatum leaves extract, treatment group 2 using 100 mg/kg BW red piper crocatum leaves extract, treatment group 3 using 150 mg/kg BW red piper crocatum leaves extract, and treatment  group 4 200mg/kg BW red piper crocatum leaves extract. Results : It was observed that intake of 150 mg/B  red piper crocatum leaves extract results in the highest significance decrease of 45.63% of TNF- ? levels from (28.62 ±  1.25 to 15.56 ± 7.20 ?g/mL) and a significance decrease of 15.42% of IL-6 level from (134.64 ± 1.98 to 113.87 ±  4.30 ?g/mL). Conclusion : It can be concluded that intake of red piper crocatum leaves extract acts as antiinflammation for Wistar rats with atherosclerosis through decrease of TNF- ? and IL-6 levels. Further research is  required to determine whether the application of red piper crocatum leaves extract on human will result in similar  effects of anti-inflammation.
Keywords: Consumption habit, instant food, dyslipidemia, atherosclerosis, red piper crocatum leaves extract.